1996
DOI: 10.1089/cmb.1996.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Inference from Samples of DNA Sequences with Recombination

Abstract: The sampling distribution of a collection of DNA sequences is studied under a model where recombination can occur in the ancestry of the sequences. The infinitely-many-sites model of mutation is assumed where there may only be one mutation at a given site. Ancestral inference procedures are discussed for: estimating recombination and mutation rates; estimating the times to the most recent common ancestors along the sequences; estimating ages of mutations; and estimating the number of recombination events in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
306
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(311 citation statements)
references
References 19 publications
1
306
0
4
Order By: Relevance
“…The simulation generates the ancestral recombination graph (Griffiths and Marjoram 1996) for one or more chromosome regions linked to the SDR. That graph is then used to determine the coalescence time at the site(s) of interest.…”
Section: Modelsmentioning
confidence: 99%
“…The simulation generates the ancestral recombination graph (Griffiths and Marjoram 1996) for one or more chromosome regions linked to the SDR. That graph is then used to determine the coalescence time at the site(s) of interest.…”
Section: Modelsmentioning
confidence: 99%
“…Some statistical approaches have attempted to incorporate haplotype structure directly into association tests for this purpose [14,21,15,12]. An alternative strategy is to characterize the haplotype structure in a recombining population independently of its application to a particular association test, a strategy that has been pursued from many directions [11,7,26,27,25,28,3,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…7 and 8) has confirmed the presence of recombination hotspots. Although more recent population genetic modeling efforts (9)(10)(11) have included recombination hotspots, these methods, like their predecessors (12)(13)(14)(15)(16), assume that the recombination rate is (i) homogeneous across the population, and (ii) constant throughout time. However, sperm typing has also demonstrated that some hotspots are heterogeneous in the population (17).…”
mentioning
confidence: 99%